The Modern State of Geographical Studies on the Problems of Peripherality in Ukraine - Roman Lozyns’kyi (Barometr Regionalny)
The modern state of geographical studies on problems of peripherality in Ukraine has been analyzed. Three main factors which influence the intensity of carrying out such studies were determined: the influence of Soviet and Russian geographical science; the connection between studies of peripherality and the scientific range of economic-depression problems; and the specific features of the modern development of Ukrainian human-geography. The general features of a study of this range of problems in Ukraine at the regional and global level; structural characteristics of center, semi-periphery and periphery; and approaches by Ukrainian scientists have been described in relation to the mechanisms of forming peripherality, along with methods for its study and criteria of selection.